Praças públicas e sustentabilidade da cidade - Silva, Carlos Fabrício Rocha da (2010)
This paper aims to analyze the importance of sustainability in the public squares of the city of Aracaju. These concerns fall, today, in the concerns arising from the contemporary environmental crisis and the participation of cities in this context. Within an environmental perspective, our goal is to describe and analyze how the public open spaces, squares, or do not contribute to sustainability of the city. In this sense, we seek to understand through research and environmental perception of the various appropriations that occur in these public spaces. Therefore, to perform this research we used the following approaches: a) quantitative, through the requirement of the definition of the sample to be analyzed (number of squares to be defined) and also through a survey of the presence or absence of structures and equipment in the streets b) descriptive, since they feature individually selected squares, c) qualitative, since it is the perceptions of the researcher and the patrons of these places through interviews. Among the findings highlighted the fact that leisure be present in all the squares of the research to a greater or lesser degree, always present but also the attitude of some patrons who care for a space that rightfully belongs to him, carefully and zeal, reaffirmed the importance of an identity with cultural values present in certain squares of research.